2009
DOI: 10.1590/s0037-86822009000600015
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da transmissão da leishmaniose tegumentar americana no Distrito Federal

Abstract: O objetivo do estudo foi caracterizar a leishmaniose tegumentar em pacientes do Distrito Federal, investigar infecção subclínica nos moradores das localidades dos pacientes e identificar as espécies de flebotomíneos e leishmanias. Foram selecionados pacientes atendidos no Hospital Universitário de Brasília de agosto de 2006 a junho de 2007. Parentes e vizinhos dos mesmos foram submetidos à intradermorreação de Montenegro e imunofluorescência indireta. Foram capturados flebotomíneos nas localidades de origem do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…This case profile is like those observed in a previous epidemiological study conducted in the state [15], which observed that most cases occured in people between 31.6 to 34.5 years old [18,19]. The results also demonstrate a predominance of single CL lesions, which is in accordance with other studies conducted in the Amazon [19,20] and Pará [21].…”
Section: Discussionsupporting
confidence: 91%
“…This case profile is like those observed in a previous epidemiological study conducted in the state [15], which observed that most cases occured in people between 31.6 to 34.5 years old [18,19]. The results also demonstrate a predominance of single CL lesions, which is in accordance with other studies conducted in the Amazon [19,20] and Pará [21].…”
Section: Discussionsupporting
confidence: 91%
“…The mean abundance recorded in pigsties and houses was positively associated between these sites for Lu. Whitmani , as it was already described [67, 72]. The species is anthropophilic but also an opportunistic feeder, and so the pigsties and hen houses could provide blood, shelter, and breeding places for this vector [73–75].…”
Section: Resultsmentioning
confidence: 99%
“…In the correspondence analysis, some associations between disease in pregnant women and children younger than 1-year-old and indigenous/yellow ethnicity was found. This might explain the higher susceptibility of these populations to ATL and can be linked to characteristics related to exposure to the vector and vector adaptation to the peri and/or intra-domestic areas [28].…”
Section: Discussionmentioning
confidence: 99%